Anaplastic Thyroid Carcinoma - Taccaliti, Augusto; Silvetti, Francesca; Palmonella, Gioia; Boscaro, Marco (Frontiers in Endocrinology, 2012)
Thyroid cancers represent about 1% of all human cancers. Differentiate thyroid carcinomas (DTCs), papillary and follicular cancers, are the most frequent forms, instead Anaplastic Thyroid Carcinoma (ATC) is estimated to comprise 1–2% of thyroid malignancies and it accounts for 14–39% of thyroid cancer deaths. The annual incidence of ATC is about one to two cases/million, with the overall incidence being higher in Europe (and area of endemic goiter) than in USA. ATC has a more complex genotype than DTCs, with chromosomal aberrations present in 85–100% of cases. A small number of gene mutations have been identified, and there appears to be a progression in mutations acquired during dedifferentiation. The mean survival time is around 6 months from diagnosis an outcome that is frequently not altered by treatment. ATC presents with a rapidly growing fixed and hard neck mass, often metastatic local lymph nodes appreciable on examination and/or vocal paralysis. Symptoms may reflect rapid growth of tumor with local invasion and/or compression. The majority of patients with ATC die from aggressive local regional disease, primarily from upper airway respiratory failure. For this reason, aggressive local therapy is indicated in all patients who can tolerate it. Although rarely possible, complete surgical resection gives the best chance of long-term control and improved survival. Therapy options include surgery, external beam radiation therapy, tracheostomy, chemotherapy, and investigational clinical trials. Multimodal or combination therapy should be useful. In fact, surgical debulking of local tumor, combined with external beam radiation therapy and chemotherapy as neoadjuvant (before surgery) or adjuvant (after surgery) therapy, may prevent death from local airway obstruction and as best may slight prolong survival. Investigational clinical trials in phase I or in phase II are actually in running and they include anti-angiogenetic drugs, multi-kinase inhibitor drugs.